Elaboration of Aswaja Character and Profile of Pancasila Students: Bourdieu's Social Practice Analysis - Aprilia, Bunga; Fajar, Fajar (JESS (Journal of Education on Social Science); Vol 9 No 1 (2025): Phenomenal Issues in Today's GovernmentDO - 10.24036/jess.v9i1.600, 2025)
The elaboration of Ahlussunnah Wal Jamaah (Aswaja) Character and Pancasila Student Profile (P3) is a form of unification carried out by madrasah to form noble and nationalist student characters. There is research stating that religion and nationalism are found to be in conflict in several ways. However, the relationship between religion and nationalism can be integrated through character education. The main focus of this research is to analyze the elaboration process of Aswaja and P3 characters in schools under the auspices of Islamic boarding schools and see the social practices of Aswaja and P3 character building. This article uses a qualitative approach with descriptive methods. The analysis of Aswaja and P3 character habituation practices is based on Pierre Bourdieu's social practice theory, which explains how the school environment shapes students' mindsets, attitudes, and actions. Data were collected through interviews, observations and documentation. The research findings show that the elaboration of Aswaja and P3 character education is manifested in students' social practices formed through Madrasah activities that emphasize Aswaja and P3 characters (Habitus), interactions between teachers and students and recognition of Aswaja and P3 values (Capital), and a supportive environment in madrasah (Field). Resulting in a very effective practice of habituation of student character. This is able to encourage students to be active in social activities, strengthen harmony among others, and optimize understanding of diversity.